ANTIMICROBIAL AND PHYTOCHEMICAL ANALYSIS OF LEAF EXTRACT OF MEDICINAL FRUIT PLANTS - RINKY BISHT; SHEETAL CHANYAL; Agrawal, Pavan Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The present study objective was to describe the in-vitro antimicrobial and antifungal activity of ethyl acetate extracts from leaves of papaya, pomegranate, banana and guava. , Present investigation showed that leaves extract of fruits plants are good source of bioactive compounds which have some ethnomedicinal applications were screened for their antibacterial activity against bacterial pathogen of human. Methods: A total of four plant extracts were used in this study to examine their antimicrobial properties and phytochemical analysis. Antimicrobial activity was evaluated for crude ethyl acetate extracts against human pathogen Escherichia coli, Bacillus subtilis, S<a href="https://www.google.co.in/url?sa=t&rct=j&q=&esrc=s&source=web&cd=1&ved=0ahUKEwjz4rah-MbLAhUFBo4KHVjjDCEQFggbMAA&url=https%3A%2F%2Fen.wikipedia.org%2Fwiki%2FStaphylococcus_aureus&usg=AFQjCNHeHVDrmBXUe3XjpMplqKBBJXt_NA&sig2=4mRymEMvVJgL9aIWbcNHUw&bvm=bv.117218890,d.c2E">taphylococcus aureus and Pseudomonas aeruginasa using an agar diffusion assay. Phytochemical analysis tests for the screening and identification of bioactive chemical constituents of extracts of the fruits leaf was performed. This study was also conducted to determine the total phenols present in leaf extract of fruit plants. Results : The guava leaves crude extract showed MIC of 3.75 mg/ml for B. subtilis and P. aeruginasa, which showed its efficacy as a potent antimicrobial. Phytochemical analysis of the extracts revealed the presence of bioactive compound such as saponins, alakaloids, flavonoids, terpenoids, carbohydrates and tannins. The ethyl acetate extract of banana produced highest zone of inhibition 23 mm for B subtilis. This study showed that Punica granatum leaf is a good source of phenolic compounds. Conclusion: This study concludes that these fruit leaves are potential source for bioactive metabolites and may be used in Pharmaceutical industry. On the basis of the present finding leaf extract of fruits possess the capabilities of being a good candidate in the search for a natural antimicrobial agent against infections and/or diseases caused by human pathogens. Key words: Leaves extract, Fruits, Antimicrobial activities, Antifungal activities, Minimum inhibitory concentration, Phytochemicals analysis